Production performance, egg quality, and uterine gene expression for layers as affected by N-Carbamylglutamate supplementation - Ma, Wei; Lu, Yi; Wang, Chunqiang (Frontiers in Veterinary Science, 2023)
Supplementation of exogenous additives is a strategy to improve laying performance of layers by regulating uterine function. N-Carbamylglutamate (NCG) as an activator for endogenous arginine synthesis has the potential to regulate the laying performance of layers, but its effects have not been fully understood. This study investigated the effects of dietary supplementation of NCG on production performance, egg quality, and uterine gene expression in layers. A total of 360 45-week-old layers with a genetic line of Jinghong No. 1 were used in this study. The experimental period was 14 weeks. All birds were divided into 4 treatments with 6 replicates per treatment and 15 birds per replicate. Dietary treatments were based on a basal diet and supplemented with 0, 0.08, 0.12, or 0.16% NCG to form C, N1, N2, and N3 groups. We found that layers in group N1 had higher egg production rate than those in group C. Egg weight was significantly reduced, while eggshell thickness was significantly improved, by treatment. However, the albumen height and Haugh unit were the lowest in group N3. Based on the above results, groups C and N1 were selected for further transcriptomics analysis of uterine tissue by RNA-seq. More than 7.4 Gb clean reads and 19,882 tentative genes were obtained using the Gallus gallus genome as a reference. Transcriptomics analysis in uterus tissue revealed that 95 differentially expressed genes (DEGs) were upregulated and 127 DEGs were downregulated. Functional annotation and pathway enrichment analysis showed that DEGs in uterine tissue were mainly enriched in glutathione metabolism, cholesterol metabolism, and glycerolipid metabolism, etc. Vitamin A metabolism-related gene, RBP1, nutrient transport-related gene, ALB, protein synthesis-related gene, METTL21C, and calcium transport-related gene, RYR2, CACNB2, RAMP3, and STAC, were significantly regulated by 0.08% NCG supplementation. Therefore, we concluded that NCG supplementation at a dose of 0.08% improved production performance and egg quality of layers by regulating uterus function.